(untitled) (Revista de Artes Marciales Asiáticas, 2021)
This study aimed to analyze preferred leg (PLs) and non-preferred leg (NPLs) isokinetic knee strength, lateral asymmetry ratios and to examine their correlation with static balance. Sixteen female taekwondo (TKD) athletes voluntarily participated in the study. Knee isokinetic extension (Ex) and flexion (Flx) strength were measured in concentric / concentric (Con / Con) contractions at angular velocities of 60°/s, 180°/s, and 240°/s. Ipsilateral hamstring / quadriceps (H/Q) and bilateral (H/H and Q /Q) ratios were calculated. Static balances were determined by taking the center of body pressure in X (COPX) and Y (COPY) axis. Paired sample t-test and Pearson correlation tests were used in statistical analysis. When the isokinetic knee strength was examined, it was found that 60°/s angular velocity parameter was significantly different in Flx phase while 180°/s and 240°/s angular velocities were found to be significantly different in Ex phase in favor of PLs. There was no significance in bilateral and ipsilateral strength ratios of all angular velocities. There was a significant correlation between 240°/s HQ and COPX in terms of ipsilateral asymmetry ratios whereas a significant correlation was found between 60°/s HH and COPX in terms of bilateral asymmetry ratios. It was found that there were differences in strength between PL and NPLs, but no asymmetry was observed. There was no high level of correlation between lateral asymmetry ratios and balance in female TKD practitioners.